The Early Islamic Mining Boom - Morony, Michael (Journal of the economic and social history of the Orient, 2019)
Abstract The present article shows that, according to archaeological and literary evidence, an expansion in mining occurred in the early Islamic world as a result of changes in mining technology at the end of Late Antiquity. The production of gold, silver, copper, iron, and other minerals is shown to have peaked in the eighth and ninth centuries and then to have declined during the tenth and eleventh centuries due to insecurity and/or exhaustion of the mines. Mining development was financed privately, and mines were usually private property.